2013
DOI: 10.1007/s40477-013-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

CEUS in the study of bladder, method, administration and evaluation, a technical note

Abstract: Purpose Contrast-enhanced ultrasound (CEUS) is the application of ultrasound contrast agents (UCAs) to traditional medical sonography. The development of UCAs allowed to overcome some of the limitations of conventional B-mode and Doppler ultrasound techniques and enabled the display of the parenchymal microvasculature. Purpose of this paper is to delineate the elements of a solid and science-based technique in the execution of urinary bladder CEUS. Methods We describe the technical execution of urinary bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…If Ta and T1 lesions were combined as NMIBC, then the sensitivity of the test improved but specificity declined. Our results are in concordance with previously published studies [9, 10, 11]. …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…If Ta and T1 lesions were combined as NMIBC, then the sensitivity of the test improved but specificity declined. Our results are in concordance with previously published studies [9, 10, 11]. …”
Section: Discussionsupporting
confidence: 94%
“…The software that is used for the quantitative analysis a CEUS recording is different with different manufacturers [10, 11]. There are many types of propriety software available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent rapid development of contrast‐enhanced ultrasound (CEUS) has increased the clinical value of ultrasound in oncology by providing quantification of tumor blood perfusion parameters . It has already been suggested that CEUS has the potential for differentiating low‐grade bladder urothelial carcinoma from high grade . Contrast‐enhanced ultrasound is a diagnostic method that enables the assessment of tumor microvasculature via blood pool imaging, and has been used for studying angiogenesis in solid pancreatic lesions and liver tumors .…”
mentioning
confidence: 99%
“…12 It has already been suggested that CEUS has the potential for differentiating low-grade bladder urothelial carcinoma from high grade. 13,14 Contrast-enhanced ultrasound is a diagnostic method that enables the assessment of tumor microvasculature via blood pool imaging, and has been used for studying angiogenesis in solid pancreatic lesions and liver tumors. 15,16 Thus, CEUS may be suitable for the evaluation of bladder urothelial carcinoma angiogenesis.…”
mentioning
confidence: 99%